Criminal Responsibility For Determination Of Suspects Of Duck Theft Assault Through Video Recording Evidence Obtained From Whatsapp At Labuhanbatu Police - Muhammad Rizkiyawan Rafiyanto; Risdalina Risdalina; Indra Kumalasari M (CV. AFDIFAL MAJU BERKAH, 2025)
Criminal liability for the determination of suspects in the abuse of duck theft which is proven through video recordings that have been sent many times to the victim's family so that this is seen from the aspect of Article 184 of the Criminal Procedure Code and the aspect of Law Number 19 of 2016 concerning Electronic Transaction Information (ITE) so that the video recording evidence used as evidence by the Labuhanbatu Police investigators fulfills the elements to determine a suspect for the perpetrator without taking expert testimony and conducting a forensic test on the video recording obtained via WhatsApp as social media so that law enforcement against perpetrators of acts of violence and abuse that meet the elements of the crime that has been processed is seen to be irregular with the provisions of the applicable law in law enforcement so that the perpetrator must be held accountable for his actions through evidence of video recordings obtained through social media to determine the perpetrators as suspects, even though legal norms clearly function as guidelines for legal relations in community and state life. However, in reality, law enforcement against vigilante actions that meet the elements of Article 170 or Article 351 of the Criminal Code by Labuhanbatu Police investigators fulfilling the elements to determine the suspect for the perpetrator without taking expert testimony and conducting a forensic test on the video recording obtained through WhatsApp as social media so that law enforcement against perpetrators of acts of violence and abuse that meet the elements of a crime that has been processed is seen to be irregular with the provisions of the applicable law in law enforcement so that the perpetrator must be held accountable for his actions through evidence of video recordings obtained through social media to determine the perpetrators as suspects, even though legal norms clearly function as guidelines for legal relations in community and state life. However, in reality, law enforcement against vigilante actions that meet the elements of Article 170 or Article 351 of the Criminal Code by investigators from the Labuhanbatu Police for duck theft does not reflect the law enforcement expected for the perpetrators who force the perpetrators to be determined as suspects to be held accountable for their actions. This researcher uses the Normative Juridical research method using primary data and secondary data with the interview method as supporting data with related agencies by drawing deductive conclusions. The results of the study explain that (1) Law enforcement against vigilante actions that meet the elements of Article 170 of the Criminal Code concerning violence or Article 351 of the Criminal Code concerning abuse must be processed in accordance with applicable legal regulations in order to create law enforcement and legal certainty and justice for the victim. (2) The legal consequences of vigilante actions have resulted in the law not running properly but must be applied in accordance with the applicable legal mechanism for the investigation process so that when determining suspects for perpetrators it can be more effective so that there needs to be an increase in legal awareness in society so that society understands its rights and obligations, and law enforcement officers must improve the performance of law enforcement so that the law enforcement desired by society can be realized. (3) Criminal responsibility for the perpetrators of the duck theft assault has been determined as suspects by investigators from the Labuhanbatu Police, although in the end peace was made between the victim and the suspects as a form of responsibility for the perpetrators taking the law into their own hands for the duck theft carried out by the victim, although the victim will still be processed through the applicable law for his actions